Helping students with dyslexia and dysgraphia make connections : differentiated instruction lesson plans in reading and writing - Berninger, Virginia Wise. 4 0 16; Wolf, Beverly J.; 5 (Baltimore, Maryland : Paul H. Brookes Publishing Co., 2009)
Provides differentiated instruction lesson plans for teachers in fourth through sixth grade which are designed to help students with dyslexia, dysgraphia, or oral and written language learning disability better understand concepts in reading and writing, and includes inspiring, true stories of children who have overcome adversity.
Includes bibliographical references.
Professional.
Keywords: 2 -- 0; 6; Education. -- Dyslexic children;Students with disabilities.;Reading disability.;Learning disabilities.;Agraphia.;Handicapped children; 20; 2